The Effectivity of Humanistic Group Counselling in Improving the Psychological Well-Being of Foster Children at Orphanage - Nana Yuliana; Astiwi Kurniati; Hijrah Eko Putro (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to determine the effect of group counseling with a humanistic approach in improving the psychological well-being of foster children at the A'isyiyah Sumberrejo Orphanage, Bojonegoro Regency. The type of research used is pre-experimental research with the One Group Pretest Posttest Design model. Research subjects were selected by purposive sampling. The sample is 6 high school age foster children. The method of data collection was carried out with a psychological well-being questionnaire. Data analysis used the T test, namely the Paired Sample T Test with the help of the SPSS for Windows version 26.00 program. The results showed that the hypothesis test showed a significance value of 0.001 < 0.05, proving that there was a significant difference between the pretest with an average score of 88.67 which increased to an average score of 106.83 in the posttest. So it can be concluded that humanistic group counseling can help improve the psychological well-being of foster children in orphanages by marked changes in attitudes, understanding and positive behavior of foster children.